A study of the implications of applying a competency-based approach to performance management in a global organization - Davis, Paul (Cranfield University, 2005)
Evidence shows that an organization will function more effectively if the various components of its human resource management system are aligned and acting in a mutually supportive way (Baird and Meshoulam, 1988; Semler, 1997; Bowen and Ostroff, 2004). According to some authors a competency-based performance management system supports the concept of alignment by defining and rewarding the behaviour that is expected and associated with effective performance (Grote, 2000; Boam and Sparrow, 1992; Richards and Howard, 2004; Hopen, 2004; Mosley and Bryan, 1992). The assumptions underpinning the competency-based approach to performance management have, however, been questioned by a number of other authors, including Burgoyne (1989), Jacobs (1990), Morgan (1997) and Day, (1988). The motivation for this research study resulted from a perceived misalignment between (1) the desired leadership behaviour espoused by the top team members of a major UK multinational organization, (2) the behaviour prescribed in the organization’s leadership competencies, and (3) the behaviour that was rewarded in practice. The study takes an unusual opportunity to conduct an in-depth study of the application of a competency based approach to performance management. In the first of three linked research projects, one-to-one interviews were conducted with the organization’s six top team members using an approach that combined repertory grid and laddering techniques. The aim was firstly, to identify the top team members’ criteria 'in use' for assessing and rewarding leadership behaviour in the context of the organization's decision to utilise a competency-based approach to performance management, and secondly, to test the degree of alignment of these criteria among the top team members. The data revealed a good degree of alignment regarding the competencies required, but a poor degree of alignment on their definitions of the behaviours needed to support those competencies. It was also found that two competencies mentioned by the top team members were missing from the organization’s new formal leadership competencies. In the second project the output of Project 1 was used in a web-based questionnaire that was distributed to the 301 members of the organization’s Global Services Leadership Team (GSLT), whose performance appraisals were based on the leadership competencies. The purpose of Project 2 was firstly, to test the degree of alignment between the GSLT's views of what constituted appropriate behaviour and the views of the top team revealed in Project 1, and secondly, to test the degree of alignment of how the desired behaviours identified by the top team were seen to support the leadership competencies. The results showed a good degree of alignment across the GSLT with the top team views of what constituted appropriate behaviour but a poor degree of alignment of understanding of how those behaviours supported the formal competencies. The results also identified a degree of ambiguity within and between the competencies. In the third and final project I conducted a series of participative feedback sessions with key organizational stakeholders based on the results of Projects 1 and 2. Using principles taken from action research, Project 3 was a joint exploration of the problems identified with the performance management system exposed in Projects 1 and 2. The purpose of Project 3 was to stimulate the organization to make changes to improve the alignment and effectiveness of the performance management system. Project 3 identified that it was deemed unrealistic and inappropriate to try to define a unified set of competencies that could be applied in all contexts and applied to all of the different challenges facing the organization. The principle proposal resulting from this study is the need for a modification to alignment theory. It is proposed that extant competency literature appears to be overly prescriptive and fails to take account of contextual factors and the particular challenges facing individuals. The proposed modification to alignment theory requires the inclusion of the process of dialogue and the need for the active involvement of the leadership team members in facilitating understanding and effecting organizational alignment when applying a competency-based approach to performance management. It is proposed therefore that effective leadership action is critical to the creation of alignment that ultimately leads to more effective performance at the level of the individual, the process and the organization. Suggestions for further research to explore these proposals are made.